CULTURAL SENSITIVITIES AND LANGUAGE DIFFICULTIES IN TRANSLATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the "lingua-cultural" problems of translation, highlighting the challenges translators face when attempting to convey not only the linguisticmeaning but also the cultural context embedded in language. Key topics discussed include thedifficulties of translating idiomatic expressions, cultural references, untranslatable words, conceptual differences between cultures, and the impact of language structure on meaning. The article emphasizes the importance of cultural sensitivity and contextual understanding inthe translation process, noting that successful translation goes beyond a literal word-for-wordapproach. The conclusion underscores the ongoing relevance of human translators inovercoming these challenges, as they bridge cultural gaps and ensure effectivecommunication across languages